Long‐Lived Source Heterogeneities in the Galapagos Mantle Plume. (28th August 2018) - Gazel, Esteban; Trela, Jarek; Bizimis, Michael; Sobolev, Alexander; Batanova, Valentina; Class, Cornelia; Jicha, Brian
Abstract: Mantle plume‐derived melts provide a unique glimpse into the chemical heterogeneity of the deep mantle. However, the exact processes involved in forming and sampling lower mantle heterogeneities remain unresolved and thus, require further investigation to understand the cumulative effects of planetary differentiation, crustal recycling, and mantle mixing that lead to their formation. The Galapagos Plume is exceptional in that its lavas sample four distinct isotopic mantle components. However, the origin of each of these end‐members remains debated. In this study, we investigate the spatial and temporal appearance and evolution of these four isotopic end‐members that comprise the present‐day Archipelago by examining ancient Galapagos lava flows preserved in the accreted terranes in Costa Rica and Panama. We discovered that the spatial relationship between each of the classically defined Galapagos Domains has remained relatively constant throughout the evolution of the plume. Our new results extend the time scale of distinct isotopic heterogeneity in the source of the plume to at least 70 Ma for the Southern Domain and 90 Ma for the Central, and Northern Domains, suggesting that geochemically heterogeneous plumes rising through the mantle preserve distinct isotopic heterogeneity on the time scale of tens of millions of years. Additionally, trace element systematics of olivine crystals from the Galapagos‐related Quepos and Azuero terranes (50–70 ma) suggest derivation from sources that included recycled components. Collectively, these results suggest that mantle plumes not only sample large‐scale heterogeneities within the deep mantle, but that these source heterogeneities can remain sampled throughout the lifetime of a plume. Key Points: High‐precision olivine trace element data imply long‐lived recycled components sampled by the Galapagos plume Isotope compositions suggest that each distinct isotopic domain has been present in the plume source since its large‐igneous province stage The plume tapped these sources in the deep mantle during incipient melting and these heterogeneities became more evident upon cooling